Sense of Coherence as a Mediator in the Association Between Empathy and Moods in Healthcare Professionals: The Moderating Effect of Age - Hori, Miyo; Yoshikawa, Eisho; Hayama, Daichi; Sakamoto, Shigeko; Okada, Tsuneo; Sakai, Yoshinori; Fujiwara, Hideomi; Takayanagi, Kazue; Murakami, Kazuo; Ohnishi, Junji (Frontiers in Psychology, 2022)
While empathy is considered a critical determinant of the quality of medical care, growing evidence suggests it may be associated with both one’s own positive and negative moods among healthcare professionals. Meanwhile, sense of coherence (SOC) plays an essential role in the improvement of both psychological and physical health. Reportedly, individual SOC reaches full stability after around age 30. The aim of this study was first to evaluate the mediatory role of SOC on the association between empathy and individual moods among 114 healthcare professionals in a general hospital, and then to examine the moderating effect of age on this association. Participants completed a range of self-report demographic questionnaires, Empathy Process Scale (EPS), the 13-item Antonovsky’s SOC, and Profile of Mood States (POMS). Findings showed that SOC mediated the relations between empathy (EPS) and both POMS-Vigor (POMS-V: self-vigor mood) and POMS-Depression (POMS-D: self-depression mood). Notably, moderated mediation analysis revealed that there was a significant interaction (age × SOC) on self-vigor mood (POMS-V) in healthcare professionals. The indirect effect of empathy (EPS) on self-vigor mood (POMS-V) through SOC was significant at over mean age “32.83.” Although there was no significant interaction with age regarding the indirect effect of empathy (EPS) on self-depression mood (POMS-D), in the sub-category level analysis of empathy (EPS), we found a significant interaction item (age × empathy for other's negative affect (EPS-N)) on SOC. This indirect effect was also significant at over mean age “32.83.” Taken, together, the current study highlighted the significant mediator of SOC on that empathy amplifies self-vigor mood and attenuates self-depression mood as a protective factor among the Japanese healthcare professionals. Some components of these processes may depend on the moderating role of age, indicating that we may need to consider the SOC development with age for more effective empathy performance interventions among healthcare professionals.